Talazoparib Exposure‐Efficacy Analysis in Patients With Advanced Breast Cancer and Germline BRCA1/2 Mutations in the EMBRACA Trial. (28th May 2020) - Yu, Yanke; Elmeliegy, Mohamed; Litton, Jennifer K.; Tudor, Iulia Cristina; Czibere, Akos; Zheng, Jenny; Wang, Diane D.
Abstract: In the phase 3 EMBRACA trial, treatment with the poly(ADP‐ribose) polymerase inhibitor, talazoparib, led to significantly improved progression‐free survival (PFS) compared with chemotherapy (hazard ratio, 0.54; 95% confidence interval, 0.41‐0.71; P < .0001). We conducted an exposure‐efficacy analysis using EMBRACA data from 285 patients who were treated with talazoparib and had available pharmacokinetic parameters to evaluate the effect of talazoparib exposure (time‐varying average talazoparib concentration [Cavg, t ]) and other baseline variables on PFS. Graphical examination of the relationship between Cavg, t and PFS and a Cox proportional model were used. Exposure‐response analyses showed that higher talazoparib exposure, absence of visceral disease, lower baseline lactate dehydrogenase levels, and disease‐free interval >12 months were independent covariates associated with longer PFS. The association of talazoparib exposure with PFS (higher exposure, longer PFS) suggests the recommended starting dose of 1 mg once daily (the maximum tolerated dose) is appropriate.